2021
DOI: 10.22201/ib.20078706e.2021.92.3533
|View full text |Cite
|
Sign up to set email alerts
|

Trophic biology of the twospot livebearer, Pseudoxiphophorus bimaculatus, an invasive fish in Teuchitlán River, central Mexico

Abstract: Trophic biology of the twospot livebearer, Pseudoxiphophorus bimaculatus, an invasive fish in Teuchitlán River, central Mexico Biología trófica del guatapote manchado, Pseudoxiphophorus bimaculatus, un pez invasor en el río Teuchitlán, centro de México

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The twospot livebearer can change its diet according to alterations in habitat structure, water quality and biotic integrity (Mar‐Silva et al ., 2021). It is recognized as an omnivore and in some regions as a carnivorous‐insectivore (Carbajal‐Becerra et al ., 2020; Guzmán Santiago & Olvera Soto, 1996; Mar‐Silva et al ., 2021; Mata Salcedo, 2007; Ramírez Santillán, 2022; Trujillo‐Jiménez & Toledo Beto, 2007).…”
Section: Biology Of the Twospot Livebearermentioning
confidence: 99%
See 1 more Smart Citation
“…The twospot livebearer can change its diet according to alterations in habitat structure, water quality and biotic integrity (Mar‐Silva et al ., 2021). It is recognized as an omnivore and in some regions as a carnivorous‐insectivore (Carbajal‐Becerra et al ., 2020; Guzmán Santiago & Olvera Soto, 1996; Mar‐Silva et al ., 2021; Mata Salcedo, 2007; Ramírez Santillán, 2022; Trujillo‐Jiménez & Toledo Beto, 2007).…”
Section: Biology Of the Twospot Livebearermentioning
confidence: 99%
“…The twospot livebearer can change its diet according to alterations in habitat structure, water quality and biotic integrity (Mar‐Silva et al ., 2021). It is recognized as an omnivore and in some regions as a carnivorous‐insectivore (Carbajal‐Becerra et al ., 2020; Guzmán Santiago & Olvera Soto, 1996; Mar‐Silva et al ., 2021; Mata Salcedo, 2007; Ramírez Santillán, 2022; Trujillo‐Jiménez & Toledo Beto, 2007). There are no differences in the diets of both sexes in terms of seasonality and individual size, but it has been reported that females consume more plant‐based food than males (Trujillo‐Jiménez, 1998).…”
Section: Biology Of the Twospot Livebearermentioning
confidence: 99%
“…The twospot livebearer (Pseudoxiphophorus bimaculatus) is an omnivorous poecilid native to southern Mexico, Nicaragua, Guatemala, Belize and Honduras (Lyons, 2019) that can reach a standard length (SL) of 66 mm (Mar-Silva et al, 2021). The twospot livebearer was recently recognised as an invasive fish species present on the Mexican Central Plateau (MCP) (Gomez-Maldonado et al, 2023).…”
Section: Introductionmentioning
confidence: 99%